The Influence Of Fast Food Consumption Patterns On Adolescent Nutritional Status In The Era Of Digital Lifestyle - Muti Atun Nafi’ah; Rosmaria Rosmaria (PT. AVID MEDIA INDONESIA, 2026)
Rapid digital transformation has profoundly reshaped adolescent dietary behaviors, particularly through increased exposure to fast food advertising on social media platforms, food delivery applications, and screen-based sedentary lifestyles. This review examined the relationship between fast food consumption patterns and nutritional status among adolescents in the context of the contemporary digital lifestyle. A systematic narrative review of 20 peer-reviewed studies published between 2021 and 2024 was conducted. Findings revealed that frequent fast food and ultra-processed food (UPF) consumption were consistently associated with elevated body mass index (BMI), overweight, and obesity across multiple countries and age groups. Digital platforms amplified consumption through targeted food marketing, advergaming, and influencer endorsements that disproportionately promoted energy-dense, nutrient-poor products. Emotional eating, triggered by digital stress and social comparison, further reinforced unhealthy dietary patterns. The COVID-19 pandemic lockdowns demonstrated the acute impact of screen time intensification on adolescent weight gain. Evidence also indicates that neighborhood food environments and access to ultra-processed foods act as structural determinants of dietary quality. In conclusion, fast food consumption in the digital era constitutes a multi-layered nutritional risk for adolescents. Effective interventions require integrated strategies encompassing digital food marketing regulation, nutrition education, school-based programs, and supportive food environment policies.